An evaluation of literature related to the phenomenon of building Shrines within the residence compound among Malaysian Indians - Arumugam, H.; Subramaniam, M. (2014)

(untitled)
Hindus possess their own unique religious beliefs and practices and they have been inherited from one generation to another for centuries. Yet the religious beliefs and practices of Hindus living in India varies from that of Hindus living elsewhere or outside India. The best exemplification of the differences is the religious practice of Malaysian Hindus as they have introduced a new trend in the Hindu religious practice by building shrines for deities within their residence compound. It is a new phenomenon amongst the Malaysian Hindu community and also it is envisaged as a problem in the nation as most shrines built illegally without the consent of the local authorities. As yet no research is found on the subject and it is recommended that a study must be carried out in order to ascertain whether the building of shrines within the residence compound is permitted in theAgmnic rules of Hinduism. This article aims at looking at the literatures related to the phenomenon of establishing shrines within the residence compound which would help one to conduct a research on the above-mentioned subject